Ramucirumab plus pembrolizumab in patients with previously treated advanced non-small-cell lung cancer, gastro-oesophageal cancer, or urothelial carcinomas (JVDF): a multicohort, non-randomised, open-label, phase 1a/b trial. Issue 8 (August 2019) - Herbst, Roy S; Arkenau, Hendrik-Tobias; Santana-Davila, Rafael; Calvo, Emiliano; Paz-Ares, Luis; Cassier, Philippe A; Bendell, Johanna; Penel, Nicolas; Krebs, Matthew G; Martin-Liberal, Juan; Isambert, Nicolas; Soriano, Andres; et al.
Summary: Background: Pre-clinical and clinical evidence suggests that simultaneous blockade of VEGF receptor-2 (VEGFR-2) and PD-1 or PD-L1 enhances antigen-specific T-cell migration, antitumour activity, and has favourable toxicity. In this study, we aimed to assess the safety and preliminary antitumour activity of ramucirumab (an IgG1 VEGFR-2 antagonist) combined with pembrolizumab (an IgG4 PD-1 antagonist) in patients with previously treated advanced gastric or gastro-oesophageal junction adenocarcinoma, non-small-cell lung cancer, or urothelial carcinoma. Methods: We did a multicohort, non-randomised, open-label, phase 1a/b trial at 16 academic medical centres, hospitals, and clinics in the USA, France, Germany, Spain, and the UK. We enrolled adult patients aged 18 years or older with histologically confirmed gastric or gastro-oesophageal junction adenocarcinoma (cohorts A and B), non-small-cell lung cancer (cohort C), or urothelial carcinoma (cohort D), whose disease had progressed on one or two lines of previous therapy (for those with gastric or gastro-oesophageal junction adenocarcinoma) or one to three lines of previous therapy (for those with non-small-cell lung cancer and urothelial carcinoma) that included platinum (for all tumour types) or fluoropyrimidine or both (for gastric or gastro-oesophageal junction adenocarcinoma). Eligibility criteria included presence of measurable disease and an Eastern Cooperative Oncology Group performance status of 0–1. Patients with previously untreated gastric or gastro-oesophageal junction adenocarcinoma and non-small-cell lung cancer were also enrolled (in two additional separate cohorts); the results for these cohorts will be reported separately. The first 21-day treatment cycle was a dose-limiting toxicity observation period (phase 1a; safety run-in), followed by a phase 1b cohort expansion stage. Pembrolizumab 200 mg was administered intravenously on day 1, and intravenous ramucirumab was administered at 8 mg/kg on days 1 and 8 for cohort A or at 10 mg/kg on day 1 for cohorts B, C, and D, every 3 weeks, until disease progression or other discontinuation criteria were met. The primary endpoint was the safety and tolerability of ramucirumab in combination with pembrolizumab assessed by the incidence of adverse events in both phase 1a and 1b and as dose-limiting toxicities during phase 1a. The safety and activity analysis set included all patients who received at least one dose of study treatment. This trial is registered withClinicalTrials.gov, numberNCT02443324, and is no longer enrolling patients. Findings: Between July 30, 2015 and June 24, 2016, we enrolled and treated 92 patients (41 with gastric or gastro-oesophageal junction adenocarcinoma, 27 with non-small-cell lung cancer, and 24 with urothelial carcinoma). Median follow-up was 32·8 months (IQR 28·1–33·6). During the first cycle of treatment (phase 1a safety run-in; n=11), one patient with gastro-oesophageal junction adenocarcinoma who received the 8 mg/kg dose of ramucirumab had grade 3 abdominal pain, colitis, hepatitis, interstitial lung disease, and jaundice, and grade 4 cholestasis, and died on treatment on day 40; the death was deemed related to progressive disease. No additional dose-limiting toxicities occurred and the decision was made to maintain the full planned doses of ramucirumab and pembrolizumab in phase 1b (n=81). Treatment-related adverse events occurred in 75 (82%) of 92 patients, the most common of which was fatigue (in 33 patients [36%]), predominantly of grade 1 or 2 severity. 22 patients (24%) had one or more treatment-related adverse events of grade 3 or worse, most commonly hypertension (six patients; 7%) and colitis (five patients; 5%). Serious adverse events occurred in 53 (58%) of 92 patients, and were deemed related to treatment in 22 (24%) patients. The most common treatment-related serious adverse events were abdominal pain in patients with gastric or gastro-oesophageal junction adenocarcinoma (in three [7%] of 41 patients); asthenia and myocardial infarction in patients with non-small-cell lung cancer (two [7%] of 27 patients), and colitis in patients with urothelial carcinoma (two [8%] of 24 patients). Six (7%) of 92 patients discontinued treatment because of treatment-related adverse events, and one death (from pulmonary sepsis in a patient with gastric or gastro-oesophageal junction adenocarcinoma) was deemed related to treatment. The number of patients achieving an objective response was three (7%; 95% CI 1·5–19·9) of 41 in the gastric or gastro-oesophageal junction adenocarcinoma cohort, eight (30%; 13·8–50·2) of 27 in the non-small-cell lung cancer cohort, and three (13%, 2·7–32·4) in the urothelial carcinoma cohort. Interpretation: Ramucirumab in combination with pembrolizumab showed a manageable safety profile with favourable antitumour activity in patients with previously treated advanced gastric or gastro-oesophageal junction adenocarcinoma, non-small-cell lung cancer, and urothelial carcinoma. Our results contribute to the growing evidence that supports dual inhibition of the VEGF–VEGFR2 and PD-1–PD-L1 pathways. This combination could be further explored with or without chemotherapy, especially for patients with tumours for which single-agent checkpoint inhibitors have shown no additional benefit over chemotherapy. Funding: Eli Lilly and Company, and Merck and Co.